A spatio-temporal in-situ investigation of the Payne effect in silica-filled rubbers in Large Amplitude Oscillatory Extension. (3rd June 2022) - Staropoli, Mariapaola; Gerstner, Dominik; Duez, Benoit; Sztucki, Michael; Vehres, Guido; Radulescu, Aurel; Thomann, Jean-Sébastien; Westermann, Stephan; Pyckhout-Hintzen, Wim
Abstract: The present work deals with the structural and dynamic characteristics of a silica filler network within an industrial elastomeric composite with time-resolved Ultra-Small-Angle-X-ray Scattering (USAXS), collected for the first time in-situ under periodic uniaxial deformation. The in-situ configuration allows a unique correlation between the x-ray patterns highlighting the structure of the filler and the dynamic-mechanical stress-strain response that characterizes the full composite. A scattering model is applied to quantitatively identify the filler network evolution as a function of dynamic strain. To address the Payne effect and the underlying structural modifications correlated to intra- and inter-filler-aggregate effects, all rubbers were pre-conditioned to suppress stress-softening related to the Mullins effect. Sector-averaged scattering intensities along the parallel strain direction reveal a jamming/de-jamming transition between clusters. The dynamic stress response of the full composite shows onsets of non-linear behavior with contributions assigned to both filler and rubber phase separately. Graphical abstract: Image 1 Highlights: Scattering analysis of silica-filled SBR elastomers. Study of the Payne effect through in-situ combination of USAXS and DMA methods. Relationship between structural and dynamic-mechanical properties. Identification of jamming/de-jamming transition upon oscillatory deformation.